Advancing Stem Cell Technologies and Applications: A Special Collection from the PluriCore Network in the German Stem Cell Network (GSCN). (21st September 2020) - Besser, Daniel
Abstract: Current Protocols in Stem Cell Biology is publishing a special collection of eight articles from members of the PluriCore Network in the German Stem Cell Network. © 2020 Wiley Periodicals LLC.